(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The objective of this study was to investigate if training using instructions and modeling would improve the interaction between mothers and their children during school homework activities. Four couples of mothers and children participated in this study. The study was composed of three phases. In phase 1 mothers helped their children in the execution of school homework, in Phase 2 important concepts on how to be more effective on helping children with their school homework were taught to mothers, and in Phase 3 the intervention was removed. Results suggest that the procedure was effective only to reduce the rate of responses of the “to do for the child” category from the mother in couple 4 and, maybe, it has contributed to increase the rate of responses of the “to praise” category from the mother in couple 1. The results were compared to similar studies.